Napoleon Bonaparte's occupation of Egypt - Silfia Auziah; Yosi Nova; Rifdah Sabrina; Rosi Guspita (Sekolah Tinggi Agama Islam YDI Lubuk Sikaping, 2025)
The periodization of Islamic history is marked by periods of progress and decline, as well as periods of renewal in the Islamic world, one of which was in Egypt, which began with the arrival of Napoleon Bonaparte. The arrival of Napoleon Bonaparte certainly brought about significant changes for Muslims. The purpose of this journal is to explain that the revival of Muslims was marked by Napoleon Bonaparte's ideas and strategies in reforming Muslims in Egypt. The method used in this article is to collect data from books and journals that support the research. The results of this study show that Napoleon Bonaparte's main objectives in Egypt were to block British access to India, control the Mediterranean Sea, and introduce science to Egypt. The influence of Napoleon's expedition in Egypt brought about changes in various fields, including mental attitudes, values, politics, science and culture, as well as industry and trade. The results of this research can be used as information for students to continue to bring about change for the development of Islam.